2018
DOI: 10.12659/msm.910304
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Sexual Function in Women with Hypogonadotropic Hypogonadism Using the Female Sexual Function Index (FSFI) and the Beck Depression Inventory (BDI)

Abstract: BackgroundHypogonadotropic hypogonadism (HH), or secondary hypogonadism, results from reduced secretion of gonadotropins, including follicle-stimulating hormone (FSH) and luteinizing hormone (LH), by the pituitary gland, resulting in lack of production of sex steroids. The aim of this study was to evaluate self-reported sexual function in sexually active women with and without HH using two evaluation methods, the Female Sexual Function Index (FSFI) and the Beck Depression Inventory (BDI).Material/MethodsThe st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Sreelakshmy et al [17], showed that FSD rates were higher in people with depression regardless of severity and type. BDI was a widely used questionnaire in studies to evaluate whether there was a relationship between sexual function and depression [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Sreelakshmy et al [17], showed that FSD rates were higher in people with depression regardless of severity and type. BDI was a widely used questionnaire in studies to evaluate whether there was a relationship between sexual function and depression [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…28 Decreased levels of estrogen (menopause, turner's syndrome, premature ovarian failure and hypothalamic pituitary disease) can be associated with loss of desire, difficulty or delayed arousal, vaginal dryness and dyspareunia. [29][30][31][32][33][34][35][36][37][38][39][40][41] Testosterone levels are also associated with libio, sexual desire and arousal. Low levels of testosterone are seen to be associated with low female sexual satisfaction index.…”
Section: Endocrinementioning
confidence: 99%
“… Diamond et al 2017 [ 44 ] Cross section analysis aiming to determine the characteristics of SDs in women with PCOS vs unexplained infertility (UI) 750 women with PCOS and 900 with unexplained infertility (UI) N.A FSFI FSDS N.A MD-PHQ SF-36 FertiQoL 41.8 ± 38.0 in PCOS group vs 34.3 ± 24.6 in IU group (Mean 37.7 ± 31.6) N.A No differences in sexual function between infertile women with polycystic ovary syndrome and those with unexplained infertility, despite phenotypic and biochemical differences in androgenic manifestations. Barut et al 2018 [ 91 ] Case control 88 (42 with hypogonadotropic hypogonadism-HH) N.A FSFI BDI N.A N.A IVF In the HH group, 64.28% reported SD vs 30.34% in the control group (infertile women without HH). Shaharaki et al 2018 [ 43 ] Case–control study 164 (78 primary vs 71 secondary infertility) 115 FSFI BDI SQOL-F N.A Candidate for IVF No significant differences between fertile and infertile women.…”
Section: Infertility and Sexual Functionmentioning
confidence: 99%
“…Sexual dysfunction in couple undergoing ART is a relatively new topic, only recently explored by scientific literature. In fact, most studies on the impact of infertility in sexuality have involved couples seeking fertility care at the first assessment in infertility clinics, with no systemic evaluation of the impact of the infertility treatment program on sexual health [ 90 , 91 ]. Although a substantial agreement was detected in the recent literature, we found significant heterogeneity among the experimental protocols, mainly because of the different aims and methodologies adopted to assess sexual function (Tables 1 , 2 , 3 ).…”
Section: Sexual Function In Couples Seeking Fertility Treatment By Artmentioning
confidence: 99%